Indoor Dust as a Source of Virulent Strains of the Agents of Cryptococcosis in the Rio Negro Micro-Region of the Brazilian Amazon. (2020)
Cryptococcosis, a potentially fatal mycosis in humans, is acquired via exposure to exogenous environmental sources. This study aimed to investigate the frequency, genetic diversity, and virulence of cryptococcal strains isolated from indoor dust in the Rio Negro micro-region of the Brazilian Amazon. A total of 8.9% of the studied houses were positive, recovering nine Cryptococcus neoformans VNI and 16 C. gattii VGII isolates, revealing an endemic pattern in domestic microenvironments. The International Society for Human and Animal Mycology (ISHAM) consensus multilocus sequence typing (MLST) scheme for the C. neoformans/C. gattii species complexes identified two sequence types (STs), ST93 and ST5, amongst C. neoformans isolates and six STs amongst C. gattii isolates, including the Vancouver Island Outbreak ST7 (VGIIa) and ST20 (VGIIb), the Australian ST5, and ST264, ST268 and ST445, being unique to the studied region. Virulence studies in the Galleria mellonella model showed that five C. gattii strains and one C. neoformans strain showed a similar pathogenic potential to the highly virulent Vancouver Island outbreak strain CDR265 (VGIIa). The findings of this study indicate that humans can be exposed to the agents of cryptococcosis via house dust, forming the basis for future studies to analyze the impact of early and continuous exposure to indoor dust on the development of subclinical or clinical infections.